Did the COVID-19 Pandemic Lockdown Harm Pre-Schoolers Learning in Portugal? Yes, but with Variations Depending on Socio-Economic Status - Pedro Bem-Haja; Paulo Nossa; Diogo Simões Pereira; Carlos F. Silva (MDPI AG, 2022)
The literature has shown that the COVID-19 pandemic has indelibly affected student performance. However, this deterioration is not the same for all students, with students of a lower socio-economic status (SES) being the most affected. The present study aims to understand if the pandemic lockdown in the last year of pre-school impacted the learning skills considered crucial for the transition to primary school, and whether this impact was moderated by SES or a quiet place to study (QPS). A total of 11,158 students belonging to 318 Portuguese schools underwent an assessment protocol composed of writing skills, maths, and motor-control tasks. A pandemic effect was observed for writing skills, especially during the first lockdown. Said effects were found to be potentiated by SES. Regarding maths, the fall in skills was only observed to be significant for less economically advantaged children. Motor tasks suffered; however, this was without any significant effect for SES or QPS. Thus, a detrimental effect of the pandemic lockdown was found on pre-school skills, particularly pre-literary abilities, and especially during the first lockdown. SES appeared to potentiate some inequalities. In other words, skills differences between individuals with higher and lower SES increased during the pandemic, particularly in the first lockdown, due to novelty, unpredictability, and the need for quick adaptation.